The culture of data - Rodríguez, José Alberto (2026)
This article is about the importance of statisticalinformation for optimal organizational performance.“Trademark” is the key word for statistical research,and this concept was the point of view of a study conduc-ted at the University of Costa Rica about the socialperception of this institution. The need to create a culture of data for information and knowledge that allowself-evaluation and innovation processes, which serve asinput in achieving the inherent objectives in the organization is emphasize.